Proposed method of estimating the service life of building envelopes - Ortega Madrigal, Leticia; Serrano Lanzarote, Begoña; Bretones, José M. Fran (Revista de la Construcción. Journal of Construction, 2015)
The estimation of the service life of the construction elements of a building and its materials is an essential part of drawing up a realistic and economically viable maintenance program. In this regard, this paper presents a methodology to estimate the service life of the construction systems of outer walls and roofs frequently used in modern buildings. The reference document used was the ISO-15686 standard, which proposes an efficient method of estimating service life based on durability factors. However this method was designed for general application and is difficult to apply. Due to the scarce amount of reliable information available on material durability values, it was found necessary to generate a service-life database of the construction elements considered, as well as of their component materials, based on their common degradation mechanisms. Factors that affect durability were also identified and a clear procedure for evaluation was set up. The proposed method, rather than giving accurate information on service life, allows different construction systems to be compared and is thus of assistance in the project design phase. The methodology can also be used as a model for other construction elements and is transferable to other countries.